How can the healthcare system deliver sustainable performance? A scoping review. Issue 5 (24th May 2022) - Zurynski, Yvonne; Herkes-Deane, Jessica; Holt, Joanna; McPherson, Elise; Lamprell, Gina; Dammery, Genevieve; Meulenbroeks, Isabelle; Halim, Nicole; Braithwaite, Jeffrey
Abstract : Background: Increasing health costs, demand and patient multimorbidity challenge the sustainability of healthcare systems. These challenges persist and have been amplified by the global pandemic. Objectives: We aimed to develop an understanding of how the sustainable performance of healthcare systems (SPHS) has been conceptualised, defined and measured. Design: Scoping review of peer-reviewed articles and editorials published from database inception to February 2021. Data sources: PubMed and Ovid Medline, and snowballing techniques. Eligibility criteria: We included articles that discussed key focus concepts of SPHS: (1) definitions, (2) measurement, (3) identified challenges, (4) identified solutions for improvement and (5) scaling successful solutions to maintain SPHS. Data extraction and synthesis: After title/abstract screening, full-text articles were reviewed, and relevant information extracted and synthesised under the five focus concepts. Results: Of 142 included articles, 38 (27%) provided a definition of SPHS. Definitions were based mainly on financial sustainability, however, SPHS was also more broadly conceptualised and included acceptability to patients and workforce, resilience through adaptation, and rapid absorption of evidence and innovations. Measures of SPHS were also predominantly financial, but recent articles proposed composite measures that accounted for financial, social and health outcomes. Challenges to achieving SPHS included the increasingly complex patient populations, limited integration because of entrenched fragmented systems and siloed professional groups, and the ongoing translational gaps in evidence-to-practice and policy-to-practice. Improvement strategies for SPHS included developing appropriate workplace cultures, direct community and consumer involvement, and adoption of evidence-based practice and technologies. There was also a strong identified need for long-term monitoring and evaluations to support adaptation of healthcare systems and to anticipate changing needs where possible. Conclusions: To implement lasting change and to respond to new challenges, we need context-relevant definitions and frameworks, and robust, flexible, and feasible measures to support the long-term sustainability and performance of healthcare systems.